Six minute walking distance in kyphoscoliosis patients with chronic respiratory failure - Karakurt Zuhal (Multidisciplinary Respiratory Medicine, 2010)
Abstract Aim To evaluate kyphoscoliosis patients with chronic hypercapnic respiratory failure (CHRF) using the six minute walk test (6MWT) distance (6MWD) and cardio-pulmonary function tests. Method This prospective cross-sectional study was carried out in a tertiary training and research hospital in Turkey. Kyphoscoliosis patients with CHRF on home mechanical ventilation (HMV) followed in a respiratory intensive care unit (RICU) out-patient clinic were enrolled. Patients' demographics were recorded as well as transthoracic echocardiography (ECHO), 6MWD, spirometry, arterial blood gas (ABG) values and high resolution chest computed tomography. 6MWT results were compared with other parameters. Results Thirty four patients with kyphoscoliosis and chronic respiratory insufficiency admitted to our outpatient clinic were included in the study but 25 (17 M) patients underwent 6MWT (8 patients walked with oxygen supplement due to PaO2 < 60 mm Hg). The mean 6MWD was 274.4 ± 76.2 (median 270) m and median 6MWD predicted rate was 43.7% (inter quartile ratio, IQR, 37.6% to 47.7%). Median HMV use was 3 years (IQR 2-4). 6MWD predicted rate, body mass index (BMI), HMV duration were similar in male and female patients. 6MWD correlated well with age, BMI, dyspnea score for baseline 6MWT (r: - 0.59, p < 0.002, r: - 0.58, p < 0.003, r: - 0.55, p < 0.005 respectively) but modestly with forced expiratory volume in one second, pulse rate for baseline 6MWT, pulse saturation rate, fatigue and dyspnea score at end of 6MWT (r: - 0.44, p < 0.048; r: 0.44, p < 0.027; r: - 0.43, p < 0.031; r: - 0.42, p < 0.036; r: - 0.42, p < 0.034 respectively). 6MWD predicted rate was only correlated with dyspnea score at baseline (r: - 0.46, p < 0.022). The systolic pulmonary arterial pressure (PAPs) in 6 (24%) cases was more than 40 mmHg, in whom mean PaO2/FiO2 was 301.4 ± 55.4 compared to 280.9 ± 50.2 in those with normal PAPs (p > 0.40). Conclusion The 6MWT is an easy way to evaluate physical performance limitation in kyphoscoliosis patients with chronic hypercapnic respiratory failure using home mechanical ventilation. Nearly 275 m was the mean distance walked in the 6MWT, but rather than distance in meters, the 6MWD predicted rate according to gender and body mass index equation might be a better way for deciding about physical performance of these patients. Dyspnea score at baseline before the 6MWT may be the most important point that affects 6MWD in this patient population.